Menilai Kinerja Keuangan Berdasarkan Rasio Keuangan: Studi Kasus Pada PT XL Axiata, Tbk - Andriyani, Dini; Russevelty, Virania Salshabilla (INVESTASI : Inovasi Jurnal Ekonomi dan Akuntansi, 2024)
This study aims to measure the financial performance of PT XL Axiata Tbk for the 2019-2022 period using financial ratio analysis techniques. Financial ratios are figures obtained from the results of a comparison between one financial statement item and another item that has a relevant and significant relationship. Comparisons can be made between one financial statement item and another or between items between financial statement items. This scientific research uses a quantitative method, namely a data analysis technique that uses numerical calculations. In this study, the data used is secondary data, namely the annual financial report data of PT XL Axiata Tbk for the 2019-2022 period. The analysis tools used in this study use the liquidity ratio, solvency ratio and profitability ratio. The results of the study of PT XL Axiata Tbk for the 2019-2022 period show that the liquidity ratio value using the current ratio, quick ratio and cash ratio analysis tools shows a poor condition, because the company has not been able to pay current debts with the current assets it has. The solvency ratio using the debt to assets ratio and debt to equity ratio analysis tools shows a poor condition because the company cannot cover the total debt with the capital it has. And in the profitability ratio using the NPM, ROA and ROE analysis tools, the company is in a less than good condition because the company has not been able to maximize profits from the total assets it owns.